Mengenal feminisme Jawa (catatan awal dari beberapa karya sastra Jawa) - Widyastuti, Sri Harti (Kejawen, 2025)
This article is represent of feminism concept in Javanese culture. In the history, Javanese woman as subordinative than Javanese man. For example, there are many ceremonials in the Javanese palace, like tedhak sungging. In terms of Javanese there are many tales about it the story Anak Takon Bapak. The subordinative position form wife as kanca wingking. Problems of feminism are also founded in modern Javanese literature. Several of them are Anteping Tekad and Mendhung Kesaput Angin.